Cancers in elite controllers: appropriate follow-up is essential. (17th July 2016) - Okulicz, Jason F.; Boufassa, Faroudy; Costagliola, Dominique; Ganesan, Anuradha; Lambotte, Olivier
Abstract : Elite controllers may have non-AIDS-defining comorbidities. We describe here 18 cases of cancers diagnosed in two cohorts of controllers, elite and viremic. Cancers are similar to those commonly described in antiretroviral therapy treated patients but also in HIV-negative patients, which underlines the necessity of an appropriate regular follow-up.